From Islamophobia to Westophobia: The Long Road to Radical Islamism. (April 2016) - Ali, Ameer
Islamophobia or the fear of Islam in Christian West is as old as Islam itself, and Westophobia or antipathy towards the West is its younger sibling born in the wake of European colonization of Islamdom. During its high noon, Islamdom ignored the West, because the West could hardly provide anything novel or useful to enhance the strength and prosperity of the caliphate. There was thus no Westophobia in the Islamic quarter until the colonial era, but there was certainly an undercurrent of military hostility and a superiority complex because Islamdom then was a hegemon. Colonialism reversed everything. The humiliation that Islam and Muslims endured politically, economically and culturally under European colonization created contradictory responses ranging from Westernization, Westoxification and Islamization. However, the failure of the Western secular models to promote democracy and development with justice and equity, and persisting grievances against a West-manufactured world order, provoked a wave of Westophobia which in turn has produced in the West a more pernicious brand of Islamophobia. Amidst this spiralling negativism, a new generation of Islamists are becoming extremely radicalized.